Comparing the Effectiveness of Neurofeedback and Transcranial Direct Current Stimulation on Sleep Quality of Patients With Migraine - Zahra Kosari; Mohsen Dadashi; Mahdi Maghbouli; Hossin Mostafavi (Basic and Clinical Neuroscience, 2019)
Introduction: Migraine is considered one of the most common primary headache disorders. Migraine attacks may occur due to a lack of sleep. Furthermore, sleep is regarded as one of the smoothing factors of migraine pain. Patients with sleep disorders often suffer from headaches when they wake up compared with healthy individuals. Methods: This research was a quasi-experimental study with a pretest-posttest design and a 2-month follow-up. The samples included 20 migraine patients within the age range of 15 to 55 years who were selected as volunteers for treatment by the neurologists and psychiatrists during 2017. The initial evaluation was then conducted based on the inclusion and exclusion criteria and using the Ahvaz migraine questionnaire, and Pittsburgh sleep quality index. The patients were randomly assigned to two neurofeedback (n=10) and transcranial direct current stimulation (tDCS) (n=10) groups and evaluated three times. The obtained data were analyzed by the repeated measures ANCOVA and Chi-square test in SPSS. Results: Based on the scores of both groups, no significant difference was observed between neurofeedback and tDCS groups. However, based on the results, neurofeedback decreased sleep latency, whereas tDCS increased sleep efficiency. Overall, these two treatments were effective in improving subjective sleep quality and sleep quality. Conclusion: Both neurofeedback and tDCS treatments could significantly enhance sleep quality of the patients in the posttest and 2-month follow-up. Given the effectiveness of both treatments, neurofeedback and tDCS are recommended to be used for improving the sleep status of patients with migraine.